Maresin1 Alleviates Metabolic Dysfunction in Septic Mice: A 1H NMR-Based Metabolomics Analysis - Yu Hao; Hong Zheng; Ruo-Han Wang; Hui Li; Li-Li Yang; Suwas Bhandari; Yong-Jian Liu; Jun Han; Fang Gao Smith; Hong-Chang Gao; Sheng-Wei Jin (Mediators of Inflammation)
Maresin1 (MaR1), a new anti-inflammatory and proresolving lipid mediator, has been proven to exert organ-protective effects in septic animal models. However, the potential mechanisms are still not fully elucidated. In this study, we sought to explore the impact of MaR1 on metabolic dysfunction in cecal ligation and puncture- (CLP-) induced septic mice. We found that MaR1 significantly increased the overall survival rate and attenuated lung and liver injuries in septic mice. In addition, MaR1 markedly reduced the levels of proinflammatory cytokines (TNF-α and IL-6) and alleviated mitochondrial damage. Based on a 1H NMR-based metabolomics analysis, CLP-induced septic mice had increased levels of acetate, pyruvate, and lactate in serum and decreased levels of alanine, aspartate, glutamate, and fumarate in lungs. However, these metabolic disorders, mainly involving energy and amino acid metabolism, can be recovered by MaR1 treatment. Therefore, our results suggest that the protective effects of MaR1 on sepsis could be related to the recovery of metabolic dysfunction and the alleviation of inflammation and mitochondrial damage.